An evaluation of the failure modes transition and the Christensen ductile/brittle failure theory using molecular dynamics. (30th November 2018) - Christensen, Richard; Li, Zhi; Gao, Huajian
Abstract : The Christensen ductile/brittle failure theory can be interpreted in terms of the associated failure modes, those of shear bands and voids nucleation. Their conjunction is then termed as the failure modes transition and it is studied here using molecular dynamics. The test material is taken as a particular metallic glass, CuZr. First the theoretical failure criteria are evaluated and then the theoretical failure modes transition is evaluated. Both are found to perform extremely well. The overall failure theory contains three modes of failure, the two already mentioned plus a fracture criterion. A general conclusion from the work is that the voids nucleation criterion is of unusually broad relevance. Voids nucleation leads to voids growth and then further deteriorating mechanisms and ultimately failure. But the voids nucleation is the precipitating event of all that subsequently occurs in this process. Access to these capabilities is gained through the failure theory for all homogeneous, full density, isotropic materials. Only two standard testing measurements are needed to calibrate the entire failure theory, including the transitions.